2019
DOI: 10.1055/a-0877-7869
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Infrastructure of Pregnant Women With Trisomy 21 Fetuses; Metabolomic Analysis

Abstract: Recent developments in omics technologies enable physicians to examine the metabolic and epigenetic rationales behind various medical disorders whose etiological backgrounds are not clear. Metabolomics data with genomic information helps understanding the interaction between phenotypes (or diseases) and genes, transcripts, proteins, metabolites, and the environment; thus, it may be possible to predict the occurrence of certain disorders. Metabolomics analysis includes identification and quantification of small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…We strongly believe that comprehensive and extensive research can lead to a better understanding of trisomy-related comorbidities and the corresponding phenotypes [ 95 ]. In the following section, future perspectives are highlighted for T13 and T18 investigations in connection with T21 pathogenesis [ 47 , 55 , 96 , 97 , 98 , 99 , 100 ]. It is worth noting that an in vitro model for the study of trisomies other than T21 has not been reported in the literature.…”
Section: Uncoupling Oxidative Stress From the Pathogenesis Of Trisomi...mentioning
confidence: 99%
“…We strongly believe that comprehensive and extensive research can lead to a better understanding of trisomy-related comorbidities and the corresponding phenotypes [ 95 ]. In the following section, future perspectives are highlighted for T13 and T18 investigations in connection with T21 pathogenesis [ 47 , 55 , 96 , 97 , 98 , 99 , 100 ]. It is worth noting that an in vitro model for the study of trisomies other than T21 has not been reported in the literature.…”
Section: Uncoupling Oxidative Stress From the Pathogenesis Of Trisomi...mentioning
confidence: 99%
“…Metabolomic profiling was conducted as reported previously 42,43 . Briefly, A549, H1299, H358, and H838 cells were incubated with ACPA and normal medium for 24 hours and extracted using methanol:water mixture (9:1, v/v) with internal standard (IS, 1 µg/ml myristic acid D27) and analyzed by GC-MS after methoxyamination and derivatization (n = 4).…”
Section: Intracellular Metabolites Analysismentioning
confidence: 99%
“…A study conducted by Nemutlu et al used a metabolomic platform, gas chromatography–mass spectrometry (GC-MS), and liquid chromatography–quadrupole time-of-flight mass spectrometry (LC-qTOF-MS) to find possible metabolites differentiating between healthy/normal and T21 pregnancies that could confidently be used for T21 screening. This study noted significant alterations in the concentrations of l-threonic acid, beta-alanine, oxalic acid, creatinine, alpha-tocopherol, cholesterol, uracil, and 2-piperidone, associated with an increased risk of T21 occurrence [ 64 ]. All of these metabolites previously showed vital roles in fetal development, such as beta-alanine (an antioxidant), which is the building block of carnosine and has been associated with extended muscular endurance in pregnancy.…”
Section: Metabolomic Profiles As Down Syndrome Markersmentioning
confidence: 99%
“…These enzymes also eliminate mediators of oxidative stress, providing protection against brain neurodegeneration. The decreased plasma levels of uracil observed in T21 pregnancies could potentially be associated with fetal neurodegeneration and increased oxidative stress and lipid peroxidation [ 64 ].…”
Section: Metabolomic Profiles As Down Syndrome Markersmentioning
confidence: 99%